Planothidium sheathii, a new monoraphid diatom species from rivers in California, USA - Stancheva, Rosalina (Phytotaxa, 2019)
Planothidium sheathii sp. nov., a new species from rivers in California, USA, is described based on light and scanning electron microscopy. P. sheathii has broadly lanceolate to elliptic valves with obtusely rounded apices and a unique combination of morphological features, as follows: 1) cavum with broad hood aperture that flares out at the valve margin with open borders fused with the neighboring virgae on SV, 2) multiseriate striae, composed of five to six rows of same sized areolae on both valves, interrupted at valve mantle junction, and 3) areolae groups on valve mantle, with rounded areolae on RV, and rounded and elongated areolae on SV. Valve morphology of P. sheathii is discussed in comparison with similar freshwater taxa, from which the new species is clearly distinct.